Developing a Risk Index for Start-Up Businesses in SMEs Using the Fuzzy Delphi Method (FDM) - Mohamad Fauzi, Siti Nadhirah; Ghazali, Puspa Liza; Suib , Aze Fauziah; Nawi, Farah Amalina Md.; Zain, Eni Noreni Mohamad; Rohim, Rabiatul Adawiyah Abdul; Guci, Dede Ansyari (Communications in Mathematics and Applications, 2025)
The growth of business start-ups, especially small and medium-sized enterprises, has grown due to their importance in driving economic development and creating jobs. However, many people who establish businesses struggle to sustain them beyond five years and eventually close them down. The challenges entrepreneurs face during their journeys are caused by the different risks and obstacles they face. In this context, effective management of risks is necessary for entrepreneurs to recognize and reduce such risks. This research article aims to construct a risk index for start-up businesses in SMEs by achieving expert consensus on major risk elements during start-up stages using the Fuzzy Delphi Method (FDM). The study employed a questionnaire developed through semi-structured interviews with entrepreneurs. Twenty one entrepreneurs from three industries were selected as a sample for this study. Analysing data using Microsoft Excel FDM showed four major risk factors affecting start-up businesses in small and medium-sized companies: Strategic Risk, Entrepreneurial Traits, Financial Risk, and Operational Risk. Using these factors, it is possible to generate a risk model for start-up firms within SMEs, which will serve as a guideline for entrepreneurs and other stakeholders in Malaysia. In addition, this study also assigned a weightage for every risk factor based on their priority. Lastly, using the weightage and basic formulation of the composite index, a general mathematical formulation of the Enterprise Risk Management Index was developed for start-up businesses in SMEs. Therefore, it will reduce the failure rate of start-up enterprises and increase the possibility of their success.
Keywords: Fuzzy Delphi Method (FDM); Risk factors; Composite index; SMEs; Weightage